Gilaburu (Viburnum opulus L.) fruit extract alleviates testis and sperm damages induced by taxane-based chemotherapeutics - Sariozkan, Serpil; Turk, Gaffari; Eken, Ayse; Bayram, Latife Cakir; Baldemir, Ayse; Dogan, Glden (Elsevier France-Editions Scientifiques Medicales Elsevier, 2017)
In this study, it was aimed to investigate the possible protective effects of gilaburu (Viburnum opulus L., Glb) fruit extract on testis and sperm damages induced by docetaxel (DTX) and paclitaxel (PTX) chemotherapeutics in rats. Sixty adult male Wistar albino rats were divided into 6 equal groups, 10 animals each. The groups were created as control (weekly i.p. saline injection), Glb (weekly i.p. saline injection and daily oral 100 mg/kg Glb), DTX (weekly i.p. injection of 5 mg/kg DTX), PTX (weekly i.p. injection of 4 mg/kg PTX), DTX + Glb (weekly i.p. injection of 5 mg/kg DTX and daily oral 100 mg/kg Glb) and PTX + Glb (weekly i.p. injection of 4 mg/kg PTX and daily oral 100 mg/kg Glb). Following 10-week chronic application, spermatological, biochemical, histopathological, cytopathological and immunohistochemical examinations were performed. DTX and PTX caused significant decreases in absolute and relative weights of all reproductive organs, testosterone level, sperm motility, concentration, Bcl-2 anti-apoptotic immunopositive cell scores of testes and spermatozoa as well as catalase activity in epididymal tissue, superoxide dismutase and glutathione peroxidase activities of testicular and epididymal tissues when compared with the control group. Both drugs also significantly increased abnormal sperm rate, testicular and epididymal malondialdehyde level, Bax pro-apoptotic immunopositive cell scores of testes and spermatozoa, and caused remarkable testicular histological and cytological damages. However, Glb consumption mitigated the PTX-induced decreases in absolute weights of epididimis, seminal vesicles, ventral prostate and both taxanes-induced disturbances in sperm characteristics, imbalances in oxidant/antioxidant system, increments in germ cell apoptosis and testicular histo-and cyto-pathological damages. It was concluded that long-term Glb consumption alleviates the taxanes-induced damages in reproductive system of male rats.
Keywords: Apoptosis; Gilaburu; Docetaxel-paclitaxel; Oxidative stress; Sperm; Testis